(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The recurring and abrupt collapse of concrete structures as well as apparent cracks in buildings underscores the importance of this study. The research investigated the potential utilization of coconut fiber as a strengthening material to augment the load-bearing capacity of concrete. To achieve this, concrete beams measuring 600mm x 150mm x 150mm were produced, and coconut fiber was added in varying proportions of 1%, 2%, 3%, and 4% by weight as a partial substitute for cement. Load testing was carried out on the samples produced on days 7 and 28. The study revealed that concrete M40 containing coconut fibers tends to exhibit greater load resistance and is less prone to disintegration after failure compared to conventional concrete. Incorporating coconut fiber into concrete has the capability to transform the outlook of concrete by increasing its load-bearing capacity and offering an escape route in case of collapse, potentially revolutionizing the future of concrete. The superior properties of coconut fiber concrete compared to traditional concrete suggest that it can be utilized in structures designed to withstand seismic activity by introducing a 2% replacement of cement with coconut fiber to achieve greater strength.